Nursing as universal and recognisable: Nursing students'perceptions of learning outcomes from intercultural peer learning webinars: A qualitative study. (October 2017) - Carlson, Elisabeth; Stenberg, Marie; Chan, Bessie; Ho, Sukki; Lai, Timothy; Wong, Arkers; Chan, Engle Angela
Abstract: Background: Nursing students need to be prepared for the increasingly culturally diverse health care. Therefore, providing students with international perspectives remains the mission of higher education. However, given the logistic and financial constraints, not all students will be able to travel overseas for their international experiences. A feasible alternative to study abroad is internationalisation-at-home where intercultural dimensions are incorporated into curriculum, without students leaving their home universities. This paper presents findings from a collaboration between nursing programmes in Sweden and Hong Kong. The aim of the project was to explore how undergraduate nursing students' perceived achieved learning outcomes after participating in a web-based intercultural peer-learning intervention. Highlights: A generic patient case provided students with a mutual ground for reflection. International peer learning webinars enhance intercultural reflection and learning. Through collaboration, students acknowledged nursing as universal and recognisable. ICT solutions are viable for 'internationalisation at home' learning interventions.